Odpowiedzi

2010-02-01T17:56:02+01:00
A) 6(x-4)-2 = 6x-24-2 = 6x-26
b) 2(x+1)-3(x-1) = 2x+2-3x+3 = -x+5
c) -3(y-2)+2 = -3y+6+2 = -3y+8
d) 5(x-y-1)-4(x+2) = 5x-5y-5-4x-8 = x-5y-13
e) 2(3a+b)-2(a-b) = 6a+2b-2a+2b = 4a+4b
f) 1/2(4x-4)-2x = 2x-2-2x = -2
g) x(x-1)-3(x2-x) = x2-x-3x2+3x = -2x2+2x
h) 5a(a-3)-3a(a-5) = 5a2-15a-3a2+15a = 2a2
i) 3x(x+1/3y)-2y(1/2x-1/2) = 3x2+y-xy+1
2010-02-01T17:58:54+01:00
A) 6(x-4)-2 = 6x-24-2 = 6x-26
b) 2(x+1)-3(x-1) = 2x+2-3x+3 = -x+5
c) -3(y-2)+2 = -3y+6+2 = -3y+8
d) 5(x-y-1)-4(x+2) = 5x-5y-5-4x-8 = x-5y-13
e) 2(3a+b)-2(a-b) = 6a+2b-2a+2b = 4a+4b
f) 1/2(4x-4)-2x = 2x-2-2x = -2
g) x(x-1)-3(x2-x) = x2-x-3x2+3x = -2x2+2x
h) 5a(a-3)-3a(a-5) = 5a2-15a-3a2+15a = 2a(kwadrat)
i) 3x(x+1/3y)-2y(1/2x-1/2) = 3x2+y-xy+1